The Relationship between Serum Estrogen Levels and Presence of Benign Lesions in Uterus Thyroid Gland and Breasts - Tekin, Zeynep Nilufer; Demirbas, Tuna; Aycicek, Bercem; Derin Cicek, Esin (Gynecology Obstetrics & Reproductive Medicine, 2019)
Objective: We aimed to detect co-occurrence of uterine myomas, thyroid nodules and breast lesions and to investigate association between these benign tumors with estrogen levels. Study Design: In this retrospective cohort study, records of 8008 premenopausal women were analyzed who admitted to the Darıca Farabi State Hospital for routine breast image investigation and which were performed by the same radiologist between 2011 and 2016. 251 patients who had both thyroid and Pelvic Ultrasound (US) examinations in the same year were extracted from these 8008 patients. All data were obtained from file records and ICD-10 diagnosis code of electronic database of the hospital. For breast examination, breast imaging reporting and data system (BIRADS) terminology was used. Results: The mean age of the patients at the admission to the hospital was 32 ± 5.7 years. From 251 patients only 9 patients had benign lesions in all 3 organs, whereas 63 patients had both thyroid nodules and breast lesions and 5 patients had thyroid nodules and uterine myoma, and 7 patients had BIRADS 2,3 lesions and uterine myoma, respectively. We only found a relationship between age and existence of myoma uteri and thyroid nodule. (p=0.008, for both). Among hormones, only TSH (Thyroid stimulating hormone) was found to be lower in BIRADS 2,3 lesions than BIRADS 1 lesions (p=0.017). Conclusion: Our study did not show an association between estrogen levels and presence of benign lesions in different organs according to the radiologic investigation in premenopausal women.